Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1089/ars.2014.6214
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Respiratory Supercomplexes and ROS in Aging

Abstract: A better understanding on the forces affecting SC association would allow the manipulation of ROS generation, directing these species to their physiological signaling role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 418 publications
(392 reference statements)
1
77
0
10
Order By: Relevance
“…It is feasible that increasing the removal of defective mitochondria by mitophagy can lower the levels of ROS and the resultant cellular damage and its consequences in proliferating cells driven to quiescence (58). Also, in response to mitochondrial DNA damage, mitophagy is increased in a positive loop, and we found that increasing mitophagy via TIA1 and TIAR overexpression could decrease the rates of mtDNA instability.…”
Section: Discussionmentioning
confidence: 62%
“…It is feasible that increasing the removal of defective mitochondria by mitophagy can lower the levels of ROS and the resultant cellular damage and its consequences in proliferating cells driven to quiescence (58). Also, in response to mitochondrial DNA damage, mitophagy is increased in a positive loop, and we found that increasing mitophagy via TIA1 and TIAR overexpression could decrease the rates of mtDNA instability.…”
Section: Discussionmentioning
confidence: 62%
“…In light of the recent finding that remodeling of the CL fatty acyl groups does not affect mitochondrial morphology or oxidative phosphorylation (109), it is unclear whether the changes in CL molecular species have an effect on the respiratory supercomplexes. Respiratory supercomplexes are thought to play a role in the enhancement of electron flow and thereby to prevent the formation of excess oxygen radicals (78,110). Thus, it is possible that the reduced level of the supercomplexes in the pah1⌬ mutant might contribute to the elevated level of superoxide.…”
Section: Discussionmentioning
confidence: 99%
“…This was assigned to the decline in the electron transfer chain capacity, the dysfunction of respiratory complexes, the decrease in ROS scavenging enzymes, and the induction of mutations of mitochondrial DNA, which is susceptible to oxidative damage because it lacks protection from ROS and because of its proximity to them (Balaban et al., 2005; Genova & Lenaz, 2015; Hoppel, Lesnefsky, Chen, & Tandler, 2017; Kwon, Choi, Cho, & Lee, 2015). It was suggested that the accumulation of these mutations in turn deteriorates electron transfer chain function and further increases ROS production, leading to a deleterious vicious cycle.…”
Section: Regulating Factors Of Mptp and Agingmentioning
confidence: 99%